The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/bot.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Hyperextension Varus Bicondylar Tibial Plateau Fracture Pattern

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 11 publications
(7 reference statements)
1
64
1
1
Order By: Relevance
“…However, for fracture-dislocation type tibial plateau fractures, the pTSA always does not change, so we think it is more accurate to use “non-dislocated hyperextension tibial plateau fracture” to describe these hyperextension tibial plateau fracture which was mainly bone structure changes. According to the violence direction, hyperextension tibial plateau fractures are usually divided into simple hyperextension fractures, hyperextension varus fractures, and hyperextension valgus fractures [ 6 ]; according to the fracture line position, it can be divided into simple anterior compression fracture, anterior compression fracture with fracture line extending to the posterior cortical bone, and anterior compression fracture with posterior fracture fragment displacement [ 11 ]. The classification according to violence direction is more universal because it can guide treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for fracture-dislocation type tibial plateau fractures, the pTSA always does not change, so we think it is more accurate to use “non-dislocated hyperextension tibial plateau fracture” to describe these hyperextension tibial plateau fracture which was mainly bone structure changes. According to the violence direction, hyperextension tibial plateau fractures are usually divided into simple hyperextension fractures, hyperextension varus fractures, and hyperextension valgus fractures [ 6 ]; according to the fracture line position, it can be divided into simple anterior compression fracture, anterior compression fracture with fracture line extending to the posterior cortical bone, and anterior compression fracture with posterior fracture fragment displacement [ 11 ]. The classification according to violence direction is more universal because it can guide treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Jae HY et al [5] reported one case report about "anterior compression of the tibial plateau." Reza Firoozabadi et al [6] reported 25 cases of "hyperextension varus bicondylar tibial plateau fracture (HVBT)" in 2016. However, there is currently no clear definition of hyperextension tibial plateau fracture, and the previous literature reports mostly describe one of these types of features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a clinical study, complicated tibial plateau fractures with increased intra-articular density ( i.e . a fluid-liquid plane demonstrating the clinical need of nuclear magnetic resonance examination), knee injury, bone marrow cavity and torn periosteum tissue with fat and blood exudates in the joint in some patients can directly reflect the degree of knee injury[ 15 ]. Based on the principle of chemical imaging, MRI is more sensitive to changes in water molecules, and its soft tissue resolution and display efficiency are better than those of CT.…”
Section: Discussionmentioning
confidence: 99%
“…Переломы мыщелков большеберцовой кости (ББК) достаточно часто встречаются в условиях крупного города, составляя 6-10% всех внутрисуставных переломов нижних конечностей [2,7,15,17]. Двухмыщелковые переломы происходят в основном у молодых пациентов, являются следствием высокоэнергетической травмы и сопровождаются значительным повреждением мягких тканей в области коленного сустава, что обусловливает высокий процент послеоперационных осложнений [3,10,13]. На современном этапе развития травматологии превалирующим методом лечения переломов мыщелков ББК является хирургический, однако проблема стабильного функционального остеосинтеза двухмыщелковых переломов пока не решена [8,24].…”
Section: Introductionunclassified